2021
DOI: 10.1097/md.0000000000024569
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor-mutant pulmonary adenocarcinoma coexisting with tuberculosis

Abstract: Rationale: Lung cancer and pulmonary infections can have similar clinical and radiographic manifestations. Treatment for the coexistence of epidermal growth factor receptor (EGFR)-mutant pulmonary adenocarcinoma and tuberculosis remains unclear. Patient concerns: We reported a case of EGFR-mutant lung adenocarcinoma (mimicking pulmonary infections) that coexisted with pulmonary tuberculosis during the course of the disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Patients with drugresistant TB or with LC often exhibit gene mutations associated with drug resistance, which may promote the occurrence of LC-PTB comorbidity. For instance, previous studies have revealed a potential link between TB and EGFR gene mutations leading to LC drug resistance [73,74]. In drug-resistant populations, significant increases in phosphatase and tensin homolog mutations, which inhibit the tumor suppressor phosphatidylinositol 3-kinase (PI3K) pathway, have been observed.…”
Section: Analysis Of Research Trends and Frontiersmentioning
confidence: 99%
“…Patients with drugresistant TB or with LC often exhibit gene mutations associated with drug resistance, which may promote the occurrence of LC-PTB comorbidity. For instance, previous studies have revealed a potential link between TB and EGFR gene mutations leading to LC drug resistance [73,74]. In drug-resistant populations, significant increases in phosphatase and tensin homolog mutations, which inhibit the tumor suppressor phosphatidylinositol 3-kinase (PI3K) pathway, have been observed.…”
Section: Analysis Of Research Trends and Frontiersmentioning
confidence: 99%